Paleoanthropological sites of the upper Awash River basin: Fanta, Gemeda and Koche, preliminary results. (10th May 2022) - Lanzarone, Peter; Garrison, Ervan; Bobe, René; Getahun, Assiged; Assefa, Zelalem
Abstract: Ethiopia has well known paleontological and archaeological sites within the Rift Valley, but relatively little is known of the potential within the surrounding highlands. Here, we present three underexplored sites within and nearby Addis Ababa, Ethiopia's capital city: Fanta, Gemeda, and Koche. These sites were originally mapped in 2008 as part of a rescue project carried out in advance of construction at the Fanta site. As observed in surface contexts and within the modern stream cutbank, Fanta is rich in fossil and archaeological materials. The abundance of hippopotamids at this site (both on the surface and in situ ) indicates the presence of a large body of water across the paleolandscape. The site is rich in alcelaphine bovids and equids, and thus likely represents a highland grassland environment. The surface of the site is also rich in artifacts that demonstrate morphologies of the Acheulean technological complex but the relationship of the stone tools to the fauna has yet to be determined. The other sites, Gemeda and Koche are not as rich as Fanta, but may represent other important highland sites. Since discovery, the sites remain underexplored apart from a large-area ground-penetrating radar (GPR) survey at the Fanta site which revealed a vertical succession of reflection packages that have been used to interpret the nature of sedimentary deposits at and away from the exposures. We present the interpretation of previously unpublished GPR data from this survey nearest to the stream cutbank. Finally, all three sites, but especially Fanta, are under threat of destruction from urban development and encroachment, where some of the site has undergone damages and continues to face ongoing destruction. Despite this, the sites offer the opportunity to develop a center of research, education, and tourism with easy access of Ethiopia's growing and dynamic capital city.